Phytochemical Insights into Rhizophora stylosa: pH-Dependent Extraction, Antioxidant Activity, and Enzyme Inhibition Potential - Dwi Bagus Pambudi; Muhtadi Muhtadi; Maryati Maryati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
The solvent properties, including pH, highly influence the extraction efficiency of these bioactive compounds. This study investigated the effect of pH modulation in the ethanol solvent on the recovery of antioxidants from Rhizophora stylosa. Ethanolic extraction was performed on R. stylosa samples using solvents adjusted to varying pH levels (4, 8, 9, 10, and 12). The total phenolic content (TPC) and total flavonoid content (TFC) of the extracts were quantified using standard colorimetric assays. The antioxidant activity was evaluated using the DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging assay. The inhibitory activity against carbohydrate-digesting enzymes was assessed through α-amylase and α-glucosidase inhibition assays. Additionally, data mining of established natural product databases (KNApSAcK and IMPPAT) and literature was conducted to identify and catalog the known bioactive constituents of R. stylosa. The results demonstrated a significant correlation between the pH of the extraction solvent and the yields of phenolic compounds, flavonoids, and the resulting antioxidant activity. Extract obtained at pH 10 yielded the highest TPC and exhibited the strongest antioxidant activity, whereas the highest TFC was observed at pH 4. Furthermore, enzymatic inhibition assays revealed that the pH 10 extract displayed moderate α-amylase inhibitory activity (IC₅₀ = 76.7 µg/mL) but substantially weaker α-glucosidase inhibition (IC₅₀ = 190 µg/mL), demonstrating a selective inhibition profile though less potent than that of acarbose. These findings establish pH-modulated extraction as a targeted strategy to produce potent, phenolic-rich antioxidant extracts from R. stylosa, highlighting its potential for nutraceutical and pharmaceutical applications.